1991
DOI: 10.1084/jem.174.5.1103
|View full text |Cite
|
Sign up to set email alerts
|

COOH terminus of membrane IgM is essential for an antigen-specific induction of some but not all early activation events in mature B cells.

Abstract: SummaryTransfectants of mature B cell lines that bind phosphorylcholine were made in order to understand the role of the COOH terminus of the/z chain of membrane IgM (mlgM) in generation of antigen-specific signals. A chimeric receptor (I-Ac~ tail) was constructed by replacing 40 amino acids from the # COOH terminus with that of major histocompatibility complex dass II I-Aot chain. The effect of wild-type and chimeric tails were studied on representative immediate-early antigen-specific signals. The I-Aot tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…Antigen presentation first demands endocytosis of ligandreceptor complexes and then routing of these complexes through a defined endocytic pathway. Previously, we have shown that endocytosis of ligand-receptor complexes does not depend upon the # COOH terminus (16). However, as presented here, the complete TM domain is essential for the ultimate outcome of this process, measured as activation of T cells.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Antigen presentation first demands endocytosis of ligandreceptor complexes and then routing of these complexes through a defined endocytic pathway. Previously, we have shown that endocytosis of ligand-receptor complexes does not depend upon the # COOH terminus (16). However, as presented here, the complete TM domain is essential for the ultimate outcome of this process, measured as activation of T cells.…”
Section: Discussionsupporting
confidence: 55%
“…The extracellular NH2 terminus of mIgM endows it with antigen specificity, whereas the membrane-associated COOH terminus, in concert with associated proteins, appears to be 1 Abbreviations used in this pala, r: DSM, domain shuffle mutagenesis; HEL, hen egg lysozyme; Id, idiotype; mIgM, membrane immunoglobulin M; PKC, protein kinase C; TM, transmembranal. involved in initiating the cascade of reactions mentioned above (14). We have shown that the COOH terminus is required for antigen-specific induction of intraceilular Ca 2 + levels, induction of immediate early gene messages, and growth arrest in CH33 cells (15), but not for endocytosis of ligandreceptor complexes (16). This was achieved by replacing 40 amino acids of the COOH terminus of mlgM with the equivalent segment from the COOH terminus of MHC class II I-Abol (17).…”
mentioning
confidence: 99%
“…Although these experiments suggest an important role for the Igol-IgB complex in signal transduction, the key questions of how the Igs are linked to the associated proteins, and whether Igct and Ig3 mediate signaling in B cells have not been resolved. To address these issues we have examined B cell lines that carry Igs with specific transmembrane mutations that impede signal transduction (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Several experimental studies showed that mutation of mIgM-Tyr463 and mIgM-Ser464 to valines (YS/VV) results in uncoupling of mIgM from Ig-α/Ig-β (10, 11, 61, 62). Thus, at least one of these two residues probably plays a key role in mIgM—Ig-α/Ig-β association.…”
Section: Resultsmentioning
confidence: 99%